Creativity and Resilience as a Sign of Psychic Wealth against Trauma - Rodado, Juan; Rodado, María José (Research Highlights in Disease and Health Research Vol. 2, 2023)
In this chapter, the story of a boy, called Jaime, who has suffered emotional deprivation at a young age is described. A child who had mental representations of both his family and the non-family world. In addition, the psyche of Jaime could be considered and open system if we consider the concepts of determinism and chance that appear in the introduction of this paper. The clinical case also shows the plasticity of the psyche which in the relational relationship is expressed as a capacity for improvisation. And it presents someone who has a capacity for subjectivity.